Development of sputtered SrBi2Ta2O9 thin films for nonvolatile random access memory application - Li, Yibin (2008)
Utilization of ferroelectric thin films for nonvolatile random access memory (NvRAM) applications has been under intensive investigation. Films for transistor-type memory require possessing these properties: a large remnant polarization, a low coercive field (2Ec), sufficient fatigue endurance against repetitive polarization switching. Layered perovskite structure SrBi2Ta2O9 (SBT) thin film has attracted ever increasing attention because it exhibits fatigue-free property up to 1012 cycles (even on Pt bottom electrode), excellent retention characteristics, and low leakage current density. However, two shortcomings are involved in SBT thin films: the low remnant polarization (2Pr<10?C/cm2) and high annealing temperature (>800?). Substitution at A or B site can effectively modify polarization properties. Trivalent elemental substitution such as Bi3+, La3+ and Nd3+ with the Sr2+ site induces A-site cation vacancies to satisfy charge neutrality, which significantly improves the low-field polarization.